(untitled) - Desrina, Haryadi (Netherlands, 2014)
This thesis aimed to investigate the possible role of Dendronereis spp. in the transmission of WSSV in shrimp ponds. The significance of the findings may provide new insight on the persistence of WSSV in the pond environment and novel strategies for disease management. The investigation started with a survey to determine the occurrence of WSSV in Dendronereis spp. in Indonesia, followed by subsequent laboratory observations to determine the role of Dendronereis spp. in white spot syndrome disease development.
Keywords: Tôm,Shrimps; Bệnh,Diseases